Numerical study on a supercritical vortex drop shaft with a spiral inlet - Gaetano Crispino; Filomena Maietta; Michele Iervolino; Corrado Gisonni (Results in Engineering)
Vortex drop shafts are special structures through which a nearly horizontal free-surface flow is forced to rotate and turn into a swirling flow across the vertical shaft. The existing design criteria do not allow to estimate specific design parameters, such as the maximum pressure force acting on the shaft wall, and some advance in modelling the swirling flow velocity field is still needed for supercritical approaching flows. The present research provides new experimental data related to the flow field establishing across the vertical shaft. The study describes a CFD modelling, based on 3D Volume-Of-Fluid numerical simulations, of supercritical vortex drop shafts. The geometrical configuration of the physical model of a vortex drop shaft, previously investigated in the literature, was replicated. Numerical modelling phases, from the validation to the description of the experimental activity, are described in the paper. The experimental program was designed to observe the hydraulic features of the swirling flow by changing the flow discharge in two structures of different vertical shaft diameter. It was shown that the flow behaviour inside the shaft varied significantly depending on the capacity Froude number, and it was far from being respectful of the axis-symmetry condition. The vertical distributions of the axial and tangential velocity components helped to define the shaft region along which the flow rotation almost disappeared. New insights on the pressure forces acted by the swirling flow across the vertical shaft were also provided. The numerical modelling served, therefore, as a valid complement to the standard physical model investigations.